Coupling of helix E-F motion with the O-nitrito and 2-nitrovinyl coordination in myoglobin - Ioannou, Androulla; Lambrou, Alexandra; Daskalakis, Vangelis; Pinakoulaki, Eftychia (My University, 2017)
Myoglobin (Mb) is known to react slowly with nitirite to form the green pigment by NO2− cordination to the heme Fe in the O-binding nitrito (O1[sbnd]N[dbnd]O2) mode and to the heme 2-vinyl position. Nitrite is a powerful oxidizing agent and a biological reservoir for NO that has been implicated in a variety of aerobic biological systems. Accordingly, it is important to elucidate the nature and variety of NO2− reaction mechanisms with Mb. We have performed principal component analysis (PCA, or essential dynamics) on Molecular Dynamics trajectories of all Mb[sbnd]NO2 coordination states to resolve the most important motions in the protein at 298 K. We show that the coordination or removal of NO2− to/from the heme iron is associated mainly with a motion of helix E and the coordination of NO2− to the 2-vinyl is associated with a motion of helix F and a correlated motion of helices E-F. This latter correlated motion can be attributed to the interaction of Val68 and Ile107 with the 2-nitrovinyl moiety. The resonance Raman results show that coordination of NO2− to the 2-vinyl is increased at pH 6.0 demonstrating that the amide protons in the F helix are not protected from access of solvent water and the helix F motion allows solvent access to the 2-vinyl group, without affecting the coordination to the heme Fe.
Keywords: Heme proteins; Molecular Dynamics; Nitrite; Raman spectroscopy